PERBANDINGAN PENERAPAN ESOP PADA KINERJA KEUANGANPERUSAHAAN - MARANTHIKA, JULIAN (Jurnal Akuntansi AKUNESA, 2017)
This research aimed to verify the affect of ESOP (Employee Stock OwnershipsPlan) to financial report. This research conducted due a competition phenomenonat Indonesia Stock Exchange among corporation to gain stock from the investorsin trading share. This research using quantitative and independent t-test. Thesample that used in this research are firms listed at Indonesia Stock Exchangeduring 2011-2015 that adopt ESOP or non ESOP. We used ROA (return on asset)and TATO (total asset turnover) as dependent variabels and ESOP asindependent variabel. The result indicated that ROA did not prove any different infinancial report, while TATO indicated that there is a diffrence in financial reportbetween two firms. This indicated that ESOP can’t perform earnings but ESOPcan increase sales performance. Keyword: Employee Stock Ownership Plan, Return On Asset, Total AssetTurnover.